Pengembangan Video Pembelajaran Berbasis Virtual Reality Field Trip Wilayah Pesisir Teluk Pacitan pada Pembelajaran IPS Kelas VII Tahun Pelajaran 2022/2023 - Nur Khopsun Wibowo; Esti Setiawati (UM Purwokerto Press, 2023)
The objectives of this study are to: (1) explain the procedures for creating a virtual reality field trip-based learning video in the coastal area of Pacitan Bay for Social Studies class VII for the 2022–2023 academic year; and (2) explain the efficacy of a virtual reality field trip–based learning video in the coastal area of Pacitan Bay for class VII social studies learning at SMP Negeri 2 Punung for the same year. Class VII B and class VII C acted as the experimental and control groups, respectively, in this study, which was carried out at SMP Negeri 2 Punung. The five (five) steps of the ADDIE model, which is used in this study, are the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. Participants in this study were teachers who used the materials, experts who validated the content (material experts, media experts, and learning experts), teachers of the FGD (Focus Group Discussion) MGMP Social Sciences Subject, and all students in classes VII B and VII C. Data types, both qualitative and quantitative, employed in studies on the creation of virtual reality video learning medium. The validity and appeal of the learning media are evaluated quantitatively using the results of scoring in the form of percentages, whereas the validity and appeal of the learning media are evaluated qualitatively using questionnaires, assessments, input, responses, criticism, and suggestions from material experts, media experts, learning experts, as well as document tools. teacher, teach. Additionally, in order to assess the effectiveness of using instructional media, researchers also used quantitative data in the form of student test results from the experimental class and the control class. The Paired Sample t-Test was used to test the study's hypothesis. The success of the treatment was determined by the difference between the average value before and after receiving the treatment. The study's findings included two main findings: a) the steps for creating learning media follow the ADDIE model, which consists of five stages (analysis, design, development, implementation, and assessment); and b) the ADDIE model is used to create learning media; and b) The effectiveness of the learning videos that have been created is significant because it is demonstrated by the outcomes of IBM SPSS 25 data processing, which is the value of Sig. (2-tailed) of 0.000 < 0.05, from which it can be inferred that there is a significant difference between learning outcomes and the creation of virtual reality field trip video learning media on the coast of Pacitan Bay in the Pre Test and Post Test data.